Strategi Pengembangan Perkebunan Bunga Di Kenangan Baru, Kec. Percut Sei Tuan, Kabupaten Deli Serdang, Sumatera Utara - Riris Amigo Simatupang; Hendra Saputra; Tasya Novi Ardana; Gaby P F Tampubolon; Reyka Triana Yohana Sidabutar; Indah Monalisa (Jurnal Manajemen Riset Inovasi, 2024)
Indonesia has great potential in horticulture, including floriculture, because it is one of the world's centers of biodiversity. The purpose of this research is to study the marketing strategies used by the Ibal Flower Flower Shop in Medan, North Sumatra, to sell their decorative flower products. This research uses a qualitative descriptive approach and collects data through direct observation, interviews and literature study. As a result of this research, Ibal Flower Flower Shop has succeeded in building a business that focuses on high quality products and services. However, to face increasing competition, these businesses must step up their digital marketing campaigns through e-commerce and social media platforms, hold promotional events, and collaborate with plant-loving communities. Supplier diversification, improving packaging quality, optimizing pricing, and effective inventory management are some of the suggestions for product development. Ibal Flower Flower Shop is expected to increase sales and maintain its sustainability in a dynamic market by using creative and effective marketing strategies.